Challenges of multi-professional working within one English higher education institution: 'we hit a giant': is this a shared experience?. Issue 1 (2nd January 2021) - Delahunt, Tom; Le Moine, Gayle; Soan, Sue
ABSTRACT: This paper discusses the process and outcome of an innovative qualitative research approach evidencing the lived experiences of a group of academics who were confronting what they felt at the time to be the indisputable extinction of their network. In an effort to provide a constructive response to the academics' despondency and lack of agency, one colleague, Tom, suggested using a creative approach to enable individual voices to be heard, acknowledged and appropriately shared. Utilising this consideration, the findings from a collection of personal narrative reflections were thematically analysed, snipped and re-situated in order to create a poem telling and highlighting the elements academics considered were the key drivers for their frustrations and disillusionment.